Optimization of submerged culture conditions for the production of mycelial biomass and exopolysaccharides from lignosus rhinocerus - Wei, Hong Lai; Saadiah Mohd Salleh,; Fauzi Daud,; Zamri Zainal,; Abas Mazni Othman,; Norihan Mohd Saleh, (Universiti Kebangsaan Malaysia, 2014)
Tiger’s Milk mushroom (Lignosus rhinocerus) is a highly priced medicinal mushroom utilized in traditional medicine to treat various diseases. However, due to insufficient wild L. rhinocerus, submerged culture conditions and nutritional requirements for the production of mycelial biomass and exopolysaccharide (EPS) from L. rhinocerus were studied using one-factor-at-a-time and orthogonal matrix method in shake flask culture. The optimal pH and temperature for ideal production of mycelial biomass and EPS were found to be at pH6 and 25°C, respectively. The optimal compositions for mycelial biomass production were 80 g/L of glucose, 4 g/L of potassium nitrate, 0.4 g/L of FeSO4.7H2O and 0.1 g/L of CaCI2. Subsequently, the optimal compositions for EPS production were 80 g/L of glucose, 4 g/L of potassium nitrate, 1.4 g/L of FeSO4.7H2O and 1.1 g/L of CaCI2. The maximum mycelial biomass and EPS concentrations achieved in a 1.5 L stirred-tank bioreactor were 6.3788 g/L and 1.2 g/L, respectively. Mycelial biomass production was about 3 times higher than that at the basal medium. However, EPS production indicated no significant difference at the basal medium. In addition, the concentrations for α-amylase, β-amylase, cellulase and invertase in optimal medium were 2.87, 1.07, 3.0 and 3.0 mg/mL, respectively. Current findings suggest that the production of mycelial biomass and EPS of L. rhinocerus can be enhanced dramatically by controlling the culture conditions and modifying the medium’s composition.